Presencia de hibiscus green ringspot virus (HGRV) en Cuba - Gonzalez Arias, D.=700 1 Watanabe Kitajima, E.; Beltran, A.
(Es, En)
Ilus., 13 ref.
Keywords: HIBISCUS; VIROSIS; DIAGNOSTICO; CUBA; HIBISCUS; GREEN RINGSPOT VIRUS